PENGUATAN KEMAMPUAN KERJA APARAT DESA MELALUI UJI KOMPETENSI TIK KEPADA CALON APARAT DESA - Musrifah, Ai; Abdulgani, Tarmin; Legiawan, Mohamad Kany (Politeknik Negeri Banjarmasin, 2021)
Information and communication technology (ICT) is currently an important part for supporting the process of an agency's activities. The Village Office is an agency that carries out service administration activities to the community, such as the process of making a letter of incapacity, management of resident cards, management of family cards and others related to community service administration. This process certainly does not escape the role of ICT. Therefore, the working capacity of village officials in using ICT tools must be improved. Increasing work ability through this competency test is one of the community service activities. This activity aims to improve the ability of prospective village officials to knowledge and use computers. The village partners who work together are Kademangan Village and Bobojong Village, Mande District, Cianjur Regency. The problem faced by the two partners is wanting prospective village officials who have the ability in the field of Information and Communication Technology (ICT). The method of implementing activities is by conducting a direct testing process to prospective officers which is carried out at the Basic Computer Laboratory, Informatics Engineering Study Program, Faculty of Engineering, Universitas Suryakancana. Activities carried out for three days. The results obtained from this activity were to select candidates for village officials who had competency assessments of at least 85 points as many as 5 candidates for village officials. This value is used as one of the components of the assessment of the village apparatus candidate selection committee.